Parent Education in Youth Sport: A Community Case Study of Parents, Coaches, and Administrators. Issue 4 (2nd October 2019) - Dorsch, Travis E.; King, Michael Q.; Tulane, Sarah; Osai, Keith V.; Dunn, C. Ryan; Carlsen, Chalyce P.
Abstract : The present community case study was designed to highlight parent, coach, and administrator perceptions of community-based parent education in a youth sport community in the Rocky Mountain region of the United States. Interviews with parents ( n  = 12), coaches ( n  = 13), and administrators ( n  = 11) were interpreted inductively using constructivist thematic analysis. Nine emergent categories are highlighted, including parents' sport goals for their children, parents' involvement in youth sport including impacts of involvement on children, and barriers to implementing parent education, as well as potential content for parent education. A proposed sequential framework informing community-based parent education, as well as suggestions for further action, and study limitations are included.